Schizophrenia and Toxoplasma gondii: an undervalued association? - Flegr, Jaroslav (Expert review of anti-infective therapy, 2015)
The existence of an association between schizophrenia and an infection by the protozoan parasite Toxoplasma gondii has been suspected since the 1950s. Two significant phenomena first garnered the attention of the psychiatric community toward toxoplasmosis, the illness precipitated by an infection of the parasite. Transient symptoms of acute toxoplasmosis sometimes resemble the clinical picture of paranoid schizophrenia. Many studies have also found an increased seroprevalence of toxoplasmosis in clients of mental health institutions in comparison with members of control populations. We have had to wait until the first decade of our millennium for several independent research teams to make discoveries that would shed light on the possible mechanisms that link the Toxoplasma parasite to schizophrenia.
Keywords: dopamine; manipulation hypothesis; toxoplazmóza; mental disorder; lidé; toxoplasmosis; parasite; protilátky protozoální; Antibodies, Protozoan; schizophrenia; Toxoplasmosis; Toxoplasma; Schizophrenia; schizofrenie; Humans